Grade IV oral mucositis treatment with Brazilian green propolis mucoadherent gel - Diogo Alvarenga Silva; Patrícia Carlos Caldeira; Silvia Ferreira de Sousa; Vagner Rodrigues Santos (Exploration of Drug Science)
Green propolis is collected by Apis mellifera from the flowers and buds of Baccharis dracunculifolia. It has several chemical compounds that confer anti-inflammatory, antimicrobial, healing, and antioxidant biological activities. To report a series of clinical cases in the treatment of oral mucositis (OM) in patients with cancer undergoing radiotherapy in the head and neck region. Rapid treatment of OM means restoring quality of life to patients and lowering the cost of cancer treatment for public health. There male patients with oral carcinoma undergoing radiotherapy treatment were followed between August 2018 and April 2019. The patients presented themselves to the clinics in the Faculty of Dentistry of Federal University of Minas Gerais with erythematous and ulcerated coalescing lesions with purulent fibrin pseudomembranes in the oral mucosa, classified as grade IV OM according to the World Health Organization. The patients complained about the inability to eat, drink, and speak, which caused the radiotherapy interruption. After completing the clinical forms, anamnesis, and proper oral hygiene of each patient, a mucoadherent gel containing 5% propolis was prescribed for daily use, with a 3 time-a-day application every 8 h. After 7 days of use, there was an 80% lesion reduction, with total remission after 15 days of its application. The rapid response with total remission of lesions seems to be related to the chemical composition of propolis. Clinical and cellphone monitoring of patients, weekly and daily, respectively, were essential for successful treatment. The patients were monitored for one year, being encouraged to make constant use of the gel to control hyposalivation caused by changes in the salivary glands during radiotherapy.